2021
DOI: 10.1177/0003134820968524
|View full text |Cite
|
Sign up to set email alerts
|

The Obesity Paradox in Emergency General Surgery Patients

Abstract: Operative management of emergency general surgery (EGS) diagnoses involves a range of procedures which can carry high morbidity and mortality. Little is known about the impact of obesity on patient outcomes. The aim of this study was to examine the association between body mass index (BMI) >30 kg/m2 and mortality for EGS patients. We hypothesized that obese patients would have increased mortality rates. A regional integrated health system EGS registry derived from The American Association for the Surgery o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…37 Interestingly, recent studies suggest obesity is protective against mortality in emergency abdominal operations. 38,39 Maloney et al found that when stratified by weight, overweight and obese emergency surgical patients had a decreased risk of mortality compared to normal weight emergency surgery patients and underweight individuals had the highest risk of overall mortality. 38 Similar findings were reported by Benjamin et al, which found that only underweight and morbidly obese patients experienced greater postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…37 Interestingly, recent studies suggest obesity is protective against mortality in emergency abdominal operations. 38,39 Maloney et al found that when stratified by weight, overweight and obese emergency surgical patients had a decreased risk of mortality compared to normal weight emergency surgery patients and underweight individuals had the highest risk of overall mortality. 38 Similar findings were reported by Benjamin et al, which found that only underweight and morbidly obese patients experienced greater postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Maloney et al found that when stratified by weight, overweight and obese emergency surgical patients had a decreased risk of mortality compared to normal weight emergency surgery patients and underweight individuals had the highest risk of overall mortality. 38 Similar findings were reported by Benjamin et al, which found that only underweight and morbidly obese patients experienced greater postoperative complications. 39 It has been theorized that adipose tissue plays an immunomodulatory role in the sequestration and neutralization of endotoxins thus offering protection against mortality in obese patients undergoing emergency general surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, higher BMI is associated with higher rates of thromboembolism, wound infections and blood loss perioperatively, so as to increase the in-hospital duration and the death rate after cardiac surgeries [10][11][12] . However, further in-depth studies show opposite results [13][14][15] . Overweight and obesity bene t the short-term or long-term survival after CABG [16,17] .…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, higher BMI is associated with higher rates of thromboembolism, wound infections and blood loss perioperatively, so as to increase the in-hospital duration and the death rate after cardiac surgeries [ 14 – 16 ]. However, further in-depth studies showed the opposite results [ 17 19 ]. Researchers have found the beneficial impact of overweight and obesity on the prognosis of CABG [ 20 , 21 ], which is called the “obesity paradox”.…”
Section: Discussionmentioning
confidence: 99%